The Tort Of Multimodal Transportatio Agreement - Dio Adewastia Fajaranu (Bandar Lampung University, 2015)
Multimodal transportation is one transportation system that uses more than one mode of transportation. In the Government Regulation No. 8 of 2011 on Multimodal Transportation states that multimodal transportation is transportation which uses at least two (2) different transportation modes on the basis of one (1) contract / agreement as the transport document. The problem of this research is on multimodal transportation and legal issues regarding the default under the Civil Law, Commercial Law, The Law No. 23 of 2007, The Law No. 22 of 2009, and Government Regulation No. 56 Year 2009 on the Implementation of Railways, Government Regulation No. 8 of 2011 on Multimodal Transportation. The method used juridical normative and empirical approach. This study used a source of secondary law and primary law materials, in which secondary law materials include primary data, secondary data, and the tertiary data. Primary law materials are data obtained from the results of field research on the object of research done by direct interview. This analysis conducted qualitative analysis of data in the form of information and a description that is associated with the data - other data are used to gain clarity and truth that will strengthen the existing picture. Results of research conducted at PT. KeretaApi Indonesia (Persero) Lampung region show that PT KAI in Lampung region in carrying out its operations have not been used multimodal transportation system and also in solving the problem of the tort PT. KAI resolve it amicably. As for suggestions that can be expressed by the author is that PT. KAI Lampung region immediately improve its service to solve the tort problem and improve transportation services using multimodal transportation system to facilitate the users of transportation services, and for the users of transportation services should be able to comply with all existing regulations to safeguard the security, comfort, and safety.